2010
DOI: 10.1021/jp1002808
|View full text |Cite
|
Sign up to set email alerts
|

Does PRODAN Possess an O-TICT Excited State? Synthesis and Properties of Two Constrained Derivatives

Abstract: The synthesis and photophysical properties of 7-(dimethylamino)-3,4-dihydrophenanthren-1(2H)-one (7) and 3-(dimethylamino)-8,9,10,11-tetrahydro-7H-cyclohepta[a]naphthalen-7-one (8) are reported. These compounds possess a cycloalkanone substructure that controls the extent of twisting of the carbonyl group. The six-membered ring in 7 forces the carbonyl group to be coplanar with the naphthalene ring, whereas the seven-membered ring in 8 induces a significant twist. Both have the substructure of PRODAN (6-propio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…The fluorescence of these dyes has dual character and is described in terms of locally excited state and charge-transfer state in polar solvents [24][25][26][27][28]. There is no single vision of charge-transfer state conformation among researchers: in some works it was suggested that planar molecule fluoresces, while in other it was suggested that non-planar [27,[29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence of these dyes has dual character and is described in terms of locally excited state and charge-transfer state in polar solvents [24][25][26][27][28]. There is no single vision of charge-transfer state conformation among researchers: in some works it was suggested that planar molecule fluoresces, while in other it was suggested that non-planar [27,[29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the TICT state was considered as an inconsequential artifact by some researchers . By investigating PRODAN derivatives whose dimethylamino or propionyl functional groups have been fixed in co‐planar orientation using alkylation (Figure a), several experimental studies have confirmed that the fluorescence of PRODAN originates from the LE/ICT state or LE states with charge transfer character (the planar conformation). However, it is noted that PRODAN displayed sub‐optimal quantum yields in polar solvents like water .…”
Section: Resultsmentioning
confidence: 89%
“…Nevertheless, their suboptimal and comparable quantum yields in the water–glycerol mixture (volume fractions=2/8) also validates the presence of hydrogen bond quenching (HBQ) phenomenon in PRODAN, as pointed out in previous studies . Indeed, as we changed the solvent to DMSO for avoiding hydrogen bond interactions around the oxygen atoms, the quantum yields of both P2 and P4 increased substantially (Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The correlation between the degree of quenching in an alcohol solvent, defined as log(I max /I), and Catalán’s solvent acidity parameter SA 41,45,46 is very linear. As such, the fluorescence intensity of these compounds can be used as sensors of H-bonding ability.…”
Section: Introductionmentioning
confidence: 99%